2017
DOI: 10.1038/nature21673
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between metabolic identities in the intestinal crypt supports stem cell function

Abstract: The small intestinal epithelium self-renews every four or five days. Intestinal stem cells (Lgr5 crypt base columnar cells (CBCs)) sustain this renewal and reside between terminally differentiated Paneth cells at the bottom of the intestinal crypt. Whereas the signalling requirements for maintaining stem cell function and crypt homeostasis have been well studied, little is known about how metabolism contributes to epithelial homeostasis. Here we show that freshly isolated Lgr5 CBCs and Paneth cells from the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
316
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(357 citation statements)
references
References 34 publications
16
316
0
Order By: Relevance
“…As one of the niche components, terminally differentiated Paneth cells located adjacent to Lgr5 + ISCs support Lgr5 + ISCs by secreting niche ligands. In addition to this juxtacrine interaction, by using organoids and metabolomics Rodriguez-Colman et al recently discovered that Paneth cells can also control ISC fate by dynamically supporting Lgr5 + ISC metabolism [10]. Specifically, they found that oxidative phosphorylation is distinctly active and essential in mature Lgr5 + ISCs and that glycolytic Paneth cells support oxidative Lgr5 + ISCs by supplying lactate.…”
Section: An Alternative Metabolic Niche Modulates Isc Identitymentioning
confidence: 99%
“…As one of the niche components, terminally differentiated Paneth cells located adjacent to Lgr5 + ISCs support Lgr5 + ISCs by secreting niche ligands. In addition to this juxtacrine interaction, by using organoids and metabolomics Rodriguez-Colman et al recently discovered that Paneth cells can also control ISC fate by dynamically supporting Lgr5 + ISC metabolism [10]. Specifically, they found that oxidative phosphorylation is distinctly active and essential in mature Lgr5 + ISCs and that glycolytic Paneth cells support oxidative Lgr5 + ISCs by supplying lactate.…”
Section: An Alternative Metabolic Niche Modulates Isc Identitymentioning
confidence: 99%
“…For example, in intestinal crypts (Box 1), Lgr5 + SCs have increased OXPHOS, whereas Paneth cells (Box 1) preferentially use glycolysis. Paneth cells regulate the renewal of Lgr5 + SCs by producing lactate for the oxidative metabolism of the SCs (Rodríguez-Colman et al, 2017). Apparently, high ROS levels are not harmful to intestinal SCs, but rather induce their differentiation (Yilmaz et al, 2012; Rodríguez-Colman et al, 2017).…”
Section: Metabolic Phenotypes Of Scs and Cscsmentioning
confidence: 99%
“…Paneth cells regulate the renewal of Lgr5 + SCs by producing lactate for the oxidative metabolism of the SCs (Rodríguez-Colman et al, 2017). Apparently, high ROS levels are not harmful to intestinal SCs, but rather induce their differentiation (Yilmaz et al, 2012; Rodríguez-Colman et al, 2017). Another example is satellite muscle cells (Box 1), which are localized in aerobic niches and use mainly OXPHOS; in contrast, committed progenies of these SCs undergo epigenetic reprogramming consistent with a shift to glycolytic metabolism (Ryall et al, 2015).…”
Section: Metabolic Phenotypes Of Scs and Cscsmentioning
confidence: 99%
“…Recent examination of several regenerative systems, including lymphocytes and mammary, hematopoietic, muscle, intestinal, and neural stem cells has begun to suggest that autophagy or elimination of older mitochondria, biogenesis and fusion of new organelle, along with efficient oxidative metabolism and low ROS levels are critical processes for self-renewal and cellular quiescence [2, 11, 14, 15, 18, 19, 55-57]. Reciprocally, mitochondrial stasis, aerobic glycolysis, and ROS production have been associated with greater activation, differentiation and cellular senescence.…”
Section: Bifurcating Sibling Cell Metabolism and Cell Fatementioning
confidence: 99%